Study guides

Q: How do you solve 6x plus 2 equals 1-x?

Write your answer...

Submit

Related questions

-.6x+.5x+9=-3 -.1x=-12 x=120

To solve the equation 6x plus 4-3x,first subtract 3x from 4 which leaves you with 1x. The equation now reads 6x plus 1x, which equals 7x. --- Actually, to simplify this, we have to keep the numbers multiplied with the variables from the plain numbers. The equation based on the question it this: 6X + 4 - 3X So there is a +6X a -3x and a +4. So we simplify by consolidating the numbers multiplied with the Xs. So 6X - 3X is 3X. So we have 3x + 4. There is no way to solve this since we have only part of it and no equal sign.

bringing across the =, 5x = -10 so x = -2

x2 + 6x + 8 = 0 Solve for x.X = -2 or X = -4

16x+9 without the rest of the equation, what this equals, I can't solve

If 6x + 10 = 11x , then x=2.

6x + 8 = 13, 6x = 13 - 8, 6x = 5, x = 5/6

The answer is x = 2.

4x+3x-1x = 12 Collect like terms: 6x = 12 Divide both sides of the equation by 6 to find the value of x: x = 2

If we recall that (5 cows plus 1 cow) = 6 cows, it immediately becomes apparent that5x plus 1x = 6x.

It is not possible to solve a single linear equation in two variables.

5x + x = 5x Squared (5x^2) x + x equals 2 x's = 2 = squared - very simple & logic. no its not simple and logic 5x^2 is the result of 5x times x. 5x plus x is 6x. Think of the x as 1x not x so 1x + 5x= 6x. That's simple and logic.

2x - 6x + 3x = -412x - 3x = -41-1x = -41x = 41

x=-8

x= -8

2x+6x=-9 => 8x=-9=> x=-8/9

6x +108=18y y=6x/18+108/18 y=x/3+6

-6x + 12y = -102 -6x = -12y - 102 x = 2y + 17

6x-2=x+135x=15x=3

6x+2y=4 gives y=2-(1/3)x

It works out that x = 6 and y = 3 or as (6, 3)

(0,7)

-4x+3 = 23+6x -4x-6x = 23-3 -10x = 20 x = -2

x = 6 and y = -2

4x=-10 x=-2.5